In vitro propagation and ex vitro rooting of Euonymus verrucosus Scop. (Celastraceae) – a rare species of Kazakhstan flora on the southern border of its areal. Issue 4 (4th July 2022) - Kirillov, Vitaliy; Pathak, Ashutosh; Stikhareva, Tamara; Ercisli, Sezai; Daulenova, Meirzhan; Kazangapova, Nurgul; Rakhimzhanov, Alimzhan
ABSTRACT: Euonymus verrucosus Scop. (Celastraceae) is a boreal European-Mediterranean-Asia Minor forest relict species and is listed in the Red Data Books of Kazakhstan and some regions of the Russian Federation. Thus, in the present study, in vitro regeneration of E. verrucosus utilizing young shoot explants was attempted for the first time. Initially, the young shoots (0.8–1.0 cm length) were placed in woody plant medium (WPM) and Murashige and Skoog's (MS) medium fortified with different concentrations of cytokinins, such as 6-benzylaminopurine (BAP), kinetin (Kn) and thidiazuron (TDZ), to induce axillary buds. The optimum induction was 75.0 ± 2.9% and the apical growth was 3.74 ± 0.06 cm for young shoots after 4 weeks in WPM medium supplemented with BAP (1.0 mg L −1 ). Simultaneously, during the formation of axillary shoots, callus induction was observed at the nodal base. Subculturing this callus on fresh medium every 4 weeks generated total six adventitious shoots with 0.70 ± 0.02 cm length after 12 weeks in the presence of BAP (1.0 mg L −1 ). When the adventitious shoots were isolated and transferred again to WPM medium containing 2.0 mg L −1 Kn, 2.95 ± 0.16 shoots were formed with 51.2% regeneration frequency within 4 weeks. These microshoots were then rooted ex vitro and an optimum 73.3% rooting was achieved within 4 weeks in a substrate highbog peat with a 0.5 cm layer of vermiculite. This micropropagation protocol will be helpful for the conservation of the genetic resources and biodiversity for E. verrucosus .